근거기반 정신건강 프로그램 발굴을 위한 지역사회 프로그램 현황 조사 - 안성희; 손지훈; 서화연; 이해우; 조성주; 김성남; 민혜영; 소민아; 유세영; 조성준; 박지은 (Singyŏng chŏngsin ŭihak, 2024)
Objectives This study analyzed the current state of community mental health programs in Korea to develop evidence-based criteria for these programs. Methods Seventy community mental health facilities nationwide were surveyed about the scope of their operated mental health programs. Details, including program structure, staff expertise, standardization, and quality management, of the 511 programs submitted by the facilities as their representative programs were also analyzed to evaluate their efforts for evidence-based practice. Results The average number of programs operated by community mental health welfare centers was 15.9. The most common programs were those related to serious mental illness (SMI), followed by child/adolescent mental health programs, early psychosis programs, and non-SMI adult mental health programs. In the case of community addiction management centers, there were 7.2 different addiction-related programs per center. Among the psychiatric rehabilitation facilities for SMI, the average number of programs for SMI was 13.1, with some programs for early psychosis. Of the 511 programs submitted as representative programs in their facilities, only 12.3% were judged to be good evidence-based programs. Conclusion More efforts by mental health professionals and governments are needed to implement evidence-based programs in Korea. KCI Citation Count: 0